Experience with participatory video proposals: assisting community organisations with innovation project planning. Issue 6 (18th August 2019) - Richardson-Ngwenya, Pamela; Fernandez, Raul; Restrepo, Maria J.; Kaufmann, Brigitte A.
ABSTRACT: In conventional agricultural research for development (AR4D) projects, decisions about rural innovation activities often rest with scientists. In transdisciplinary AR4D projects in Kenya and Tanzania, we designed a methodology aiming to give key decision-making rights to the farmer groups involved. Five collaborating groups were facilitated to explore different innovation possibilities and they then put forward ideas that they wished to implement. Next, the groups were invited to apply for a small grant using a video proposal. This practical note provides information on the participatory video proposal process and highlights some benefits and challenges experienced by farmers and scientists.